The Effect of Price and Service Quality on Customer Satisfaction at Cafe Tuan Jana Bandar Lampung - Aflhauranty Regina; Riswan Riswan (Cita konsultindo, 2024)
In the business world, especially in the coffee shop industry in Bandar Lampung, customer happiness is of utmost importance due to intense rivalry. The purpose of this study is to ascertain how consumer happiness at one coffee shop, Cafe Tuan Jana Bandar Lampung, is impacted by pricing and service quality. Utilizing a quantitative methodology, the study included 96 respondents who were Cafe Tuan Jana Bandar Lampung patrons. With the use of SPSS, a Likert scale questionnaire was used as part of the data gathering method. The study sample consisted of patrons of Cafe Tuan Jana Bandar Lampung, and the analytic used was multiple linear regression analysis. The study's findings demonstrate that pricing significantly and favorably affects consumer happiness. For example, in Cafe Tuan Jana Bandar Lampung, client satisfaction is positively and significantly impacted by service quality.